MCHALE’S POSTMODERN PERSPECTIVE IN AIMEE CARTER’S THE GODDESS TEST - Setyowati, Titis Ima (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2023)
This research study intends to reveal the postmodern features in The Goddess Test (2011), especially in the existence of the plurality of the worlds, the strategies used to construct the worlds and in its construction, the worlds under erasure. The theory that is used to analyze is the concepts of postmodern fiction by Brian McHale. The main data comes from The Goddess Test by Aimee Carter which is published in 2011. The result shows that there are plurality of the worlds and its construction of world under erasure in The Goddess Test. Therefore, The Goddess Test fulfills the postmodern fiction requirements by using McHale’s strategies to illustrate the worlds, and its construction.